Colo-cutaneous fistula following A pull-through for Hirschsprung disease, A case series - Vatche Melkonian; Luis de la Torre; Jill Ketzer; Victor Rodriguez; Alberto Pena; Andrea Bischoff (Elsevier, 2024)
Introductions: Three patients presented with a colo-cutaneous fistula from the neo-rectum to previous laparoscopic port sites, following an otherwise technically correct pull-through for Hirschsprung disease. We evaluated each case to provide guidance to pediatric surgeons on how to avoid this previously unreported complication. Case presentation: All three patients were male and had a laparoscopic-assisted pull-through for Hirschsprung disease as neonates. All patients underwent intra-operative colonic biopsies above the transition zone, that were closed using an Endoloop ligature (Ethicon), which later proved to be the source of the fistula. The fistulas manifested at variable times: ten days, six months, and five years after the index pull-through. Clinical findings were skin changes, abscess or drainage at previous laparoscopic port sites. Contrast studies were performed to diagnose the underlying pathology. Two patients had primary fistula closure with a diverting ileostomy, followed by ileostomy closure. One patient with delayed symptom presentation had a temporary ileostomy, redo pull-through, and ultimately an ileostomy closure. All three patients recovered without long term sequelae. Conclusion: The technical error in all of these cases was the utilization of an endoloop ligature for the biopsy site. Furthermore, when the biopsy is taken above a transition zone, it can be postulated that the increased physiologic back-pressure from the sphincter could lead to fistula development and propagation. As more cases are performed with minimally invasive techniques, we must be adamant about evaluating for new, previously un-encountered complications such as this one. An adequate closure of the full-thickness biopsy site could prevent this complication.